The Soil and Water Assessment Tool (SWAT) Model in the Context of Erosion Monitoring in the Batulayar Sub-Watershed Area - Mujiono, Ikha Setiawaty; Ayuba, Sri Rahayu; Jaya, Risman (Universitas Lambung Mangkurat, 2024)
This study was conducted in the Batulayar Sub-Watershed, Distrik Bongomeme, with the aim of assessing the level of erosion and evaluating the SWAT model as a tool for erosion monitoring. A mixed-method approach was employed, with data analyzed using the ArcSWAT software. The results indicated that the Batulayar Sub-Watershed experienced erosion categorized as